The Energy Efficiency Paradox of AI Hardware: Debunking GPU Power Consumption Myths - Aditya Avinash Atluri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article addresses the misconceptions surrounding Graphics Processing Units (GPUs) energy consumption in artificial intelligence applications by presenting a comprehensive analysis of their efficiency dynamics. Through an extensive collection of multiple GPU generations from Pascal to Blackwell architecture, the article demonstrates that while absolute power consumption has increased modestly, the gains in computational efficiency have been exponential. The article establishes that modern GPUs deliver substantial improvements in AI performance while maintaining a relatively modest increase in power requirements, resulting in significant net efficiency gains. Comparative analysis between traditional CPU-based computing and GPU implementations reveals that GPU-accelerated systems achieve remarkable speedups in deep learning tasks while maintaining significantly lower energy footprints. The article encompasses a thorough evaluation of infrastructure requirements, operational costs, and environmental impact across multiple research institutions, highlighting the superior efficiency of GPU-based solutions compared to CPU-only alternatives. Furthermore, the article explores the implications for synthetic data generation and training, where GPU acceleration enables transformative improvements in data generation efficiency and dramatically reduces training time. These findings challenge the prevailing narrative about GPU power consumption and demonstrate their crucial role in enabling sustainable AI development.